Construction of mobile Fidyah calculator / Arifah Fasha Rosmani - Rosmani, Arifah Fasha (UiTM Cawangan Perlis, 2016)
Fidyah is the fine for Muslims who are not able to qada (replace) their fast during the current Ramadhan month until the next Ramadhan. Fidyah can be paid in cash or in the form of food such as rice or dates, and it can only be given to poor Muslims who are permitted to accept Zakat. Mobile Fidyah Calculator is designed and developed for Muslims to get accurate calculation of Fidyah. Mobile Fidyah Calculator provides the calculation of rice in Kilogram (kg) as a person should pay Fidyah according to the type of rice they consumed. Mobile Fidyah Calculator also provides a guidance and information that help the users to increase their knowledge about Fidyah